Linear Algebra 2 Teaching Notes 2023
Linear Algebra 2 Teaching Notes 2023
Linear Algebra 2 Teaching Notes 2023
TEACHING NOTES
COURSE OUTLINE
1. Linear Transformations
2. Linear functionals and dual space
3. Eigenvalues and Eigenvectors
4. The characteristic polynomial
5. Annihilators
6. Bilinear quadratic and Harmitian forms
Definition: Let V and W be vector spaces. The mapping T from a vector space V to vector space W is a
simple rule that associates with each vector V (x ) in vector V exactly one vector y in W and this is
denoted by T ( x )= y or simply Tx= y .
Note:
(i) The vector space V is called the domain of the mapping and the set of vectors that map
onto in vector space W is called the range of the transformation.
V W
X T
Note: The mapping which does not satisfy the above definition is said to be a nonlinear transformation.
Example 1. Defining T :C 1 (1)→ C0 (1) by T ( f )=f 1 show that T is a linear transformation.
Solution
Then :
T ( f ) +T ( g)
(ii) T ( c f )=cT (f ). By definition of a linear operator and thus the mapping T satisfies both
properties of vector addition and scalar multiplication.
Solution
¿ T (x 1+ y 1 , x 2+ y 2 )
¿ [ ( x 1 + y 1 )−( x 2 + y 2 ) , ( x 1+ y 1 ) + ( x2 + y 2 ) ]
¿ [ ( x 1−x 2 ) + ( y 1− y 2) , ( x 1 + x 2) + ( y 1+ y 2 ) ]
¿ T ( x 1 , x 2 ) +T ( y 1 , y2 )
¿ T ( x ) +T ( y )
¿ T [C x ¿ ¿ 1 , C x 2 ]¿
¿ C [x ¿ ¿ 1−x 2 , x1 + x 2 ]¿
¿ CT (x ¿ ¿ 1 , x2 )¿
¿ CT (x )
Thus TC ( x )=CT ( x)
Exercise
[ 12 3 −1
1 5 ]
Solutions
1. From the definition of T and properties of addition and scalar multiplication, it follows that
T ( x + y )= A ( x + y)
¿ A ( x )+ A ( y )
¿ T ( x ) +T ( y )
T ( x + y )=T ( x )+T ( y )
Similarly, T ( C x ) =A ( C x )
¿ CA x
[]
x
¿
[
1 3 −1 1
2 1 5
x2
x3
]
¿
[ x 1+3 x 2−x 3
2 x 1+ x 2 +5 x 3 ]
This implies T ( x 1 , x 2 , x3 ) =(x 1 +3 x 2−x 3 , 2 x1 + x 2 +5 x3 )
Thus T : R 3 → R 2 is satisfied.
Question
Again considering a finite dimensional space we can let { v 1 , v2 , … , v n } be a basis for vector space V ,
then for all scalars c 1 , c2 , … , c n such that V =c 1 v 1 +c 2 v 2 +…+ c n v n. Thus applying transformation T
on vector space V we have T (V )=T (c ¿ ¿ 1 v ¿ ¿ 1+ c 2 v 2+ …+c n v n )¿ ¿
Example
Let T : R 2 → R 2 be a linear transformation and suppose the basis vectors v 1=(1 , 0) and v 2=(0 , 1) are
transformed as T ( v 1 )=(3 ,−2)and T ( v 2 )=(4 ,5).
Solution
x=x 1 ( 1 , 0 ) + x 2 (0 , 1)
¿ x 1 v 1+ x 2 v 2
¿ x 1 (3 ,−2)+ x 2(4 , 5)
T ( x )=¿¿
Definition: If T 1 :V →W and T 2 :V →W are two linear transformations we say that T 1=T 2 if and
only if T 1 ( v )=T 2(v ) for all v in vector space V .
The addition of two linear transformations and scalar multiplication of the same can be defined as
( T 1+ T 2 ) v =T 1 ( v ) +T 2 (v ) and it is true for all v . (cT ¿¿ 1) v=c T 1 ( v ) ∀ v ¿.
When T 1 :V →W and T 2 :V →W are linear transformations and C is a scalar then T 1+T 2 and CT 1 are
also linear transformations.
Proof
Then we have (T ¿ ¿ 1+ T 2 ) ( v 1 +v 2 ) =T 1 ( v 1 + v 2) + T 2 ( v 1 + v 2) ¿
¿ T 1( v ¿¿ 1)+ T 1 ( v 2 ) +T 2 (v ¿¿ 1)+T 2 ( v 2) ¿ ¿
¿ T 1( v ¿¿ 1)+ T 2 ( v 1 ) +T 1 (v ¿¿ 2)+T 2 ( v 2) ¿ ¿
Thus (T ¿ ¿ 1+ T 2 ) ( v 1 +v 2 ) =T 1 ( v 1 + v 2) + T 2 ( v 1 + v 2) ¿
¿ KT 1 (v)+ KT 2(v )
KT 1 ( v ) + KT 2 ( v )=K (T ¿ ¿ 1+ T 2 )v ¿
Thus the second property is satisfied. This follows that T 1+T 2 is a linear transformation.
Activity
1. Let A= [ 2 1
−1 3 ]
and B=
1 −1
2 1 [ ] 2 2 2 2
. Defining T 1 : R → R and T 2 : R → R by T 1 ( x )= Ax and
T 2 ( x )=Bx .
Find (a) T 1+T 2
(b)C T 1
When V is a vector space over a field of scalars K the mapping ∅ :V → K is called a linear functional.
Sometimes it is also referred to as a linear form if for every vector u , v ∈V and scalars a , b ∈ K the
mapping ∅ ( a u+b v )=a ∅ ( u ) +b ∅ (v ) by definition of linear form.
(a) ∅ +δ
(b) 2 ∅ −5 δ
Solution
(a) ( ∅ +δ ) ( x , y )= ∅ ( x , y ) +δ (x , y )
¿ 2 x+ y+3 x− y
¿5 x
(b) 2 ∅ −5 δ=2 ∅ ( x , y )−5 δ (x , y )
¿ 2 ( 2 x + y )−5(3 x− y )
¿ 4 x+2 y−15 x +5 y
¿−11 x+7 y
Example 2. Let V be a vector space of polynomials in t over R . Let g :V → R be the integral operator
b
defined by g ( P ( t ) ) =∫ P(t) dt where g is linear and hence it is a linear functional on V . Given that
a
1
V = { a+bt : a , b ∈ R } . Let ∅ 1 : V → R and ∅ 2 : V → R be defined by ∅ 1 f ( t )=∫ f (t)dt and
0
2
∅ 2 f ( t )=∫ f (t)dt . Find the basis { v 1 , v2 } of V which is dual to { ∅1 , ∅ 2 }.
0
Solution
Let
v 1=a+bt
v 2=c +dt }
by definition of dual basis
∅ 2 ( v 1 )=0 , ∅2 ( v 2) =1
[ ]
1 1
bt2
Case I⟹ ∅ 1 ( v 1 )=∫ ( a+bt ) dt=1 ; at + =1
0
2 0
b
a+ =1or2 a+b=2 …………………………………..(1)
2
[ ]
2 2
b t2
Again∅ 2 ( v 1 )=∫ ( a+bt ) dt=0 ; at + =0
0
2 0
[ ]
1 1
d t2
Case II ∅ 1 ( v 2 )=∫ ( c+ dt ) dt=0 ; ct+ =0
0
2 0
2 c +2 d=0orc +d=0............................(3)
[ ]
2 2
dt2
Again ∅ 2 ( v 2 )=∫ ( c+ dt ) dt=1 ; ct + =1
0
2 0
2 c +2 d=1 … … … … …..........................(4)
−1
Solving (3) and (4) gives c= and d=1
2
{ 1
}
Thus 2−2 t ,− +t becomes the basis of V which is dual to { ∅1 , ∅ 2 }
2
Example 3: Let V be a vector space of m square matrices over K and let T :V → K be a trace mapping
such that T ( A )=a 11 +a22 +…+ ann where A=(aij ). T assigns to a matrix A a sum of diagonal
elements.
Note: A set of linear functionals on a vector space V over a field of scalars K is also a vector space over
K with addition and scalar multiplication defined by ( ∅ +δ ) ( v )= ∅ ( v )+ δ(v ) and ( K ∅ ) v=K ∅ (v) where
∅ and δ are linear functionals of V and k ∈ K . This space is referred to as dual space of vector space V
¿
and the dual space of V is denoted by V
For instance: when the vector space V =K n is the vector space of n−¿turples we may write them as
¿
column vectors and the dual space V is identified with space of row vectors. Particularly any linear
functional ∅ =( a1 , a2 , … , an ) in V can be represented by
¿
()
x1
∅ ( x i )=( a1 , a 2 , ⋯ , a n ) x 2 =a1 x 1+ a2 x 2 +…+ an xn which is linear form.
⋮
x3
Dual basis
¿
Each basis of V determines the basis of the dual space V
by ∅ i ( v i ) =δ ij = {10ifif i=i ≠ jj }
Then { ∅1 , ∅ 2 , … , ∅ n } is a basis of V and δ ij is a short way of writing
¿
∅ 1 ( x , y )=ax +by
∅ 2 ( x , y )=cx + dy
Question
Considering the following basis of R3 . { v 1=( 1 ,−1 , 3 ) , v 2=( 0 , 1 ,−1 ) , v 3=(0 , 3 ,−2) }
HINT
n
Considering f (t) as a polynomial over a field of scalars K as f ( t )=an t + ⋯ +a1 t+ a0
n
If A is a square matrix over a field of scalars K we always define f ( A )=a n A + ⋯ +a 1 A+ a0 I where I
is an identity matrix.
Example 1
If A=[ ]1 2
3 4
prove that matrix A is a root of
Solution
¿2
[ 13 24 ][ 13 24]−[39 126 ]+[70 07 ]
¿2
[ 157 1022]−[−49 65 ]
¿
[1430 2044]−[−49 65]
¿
[1821 1439]
In this case A is not a root of the polynomial f ( t )=2 t 2−3 t+7
¿
[13 24 ][ 13 24 ]−[155 1020]+[ 20 02]
¿
[157 1522]−[ 105 1520 ]+[ 20 02]
¿
[00 00]
In this case A is a root of the polynomial g ( t )=t 2 −5t−2
Example 2
Solution
Since A= [ ]
1 4
2 3
and f ( t )=t 2−4 t−¿5 ,
[ ] [ ] [ ]
2
1 4 1 4 1 0
¿ −4 −5
2 3 2 3 0 1
¿
[12 43 ][ 12 43]−[ 48 1612]−[ 50 05]
¿
[00 00]
Example 3
Solution
[ ] [ ] [ ]
2
1 −2 1 −2 1 0
¿ −3 +7
4 5 4 5 0 1
¿
[ 14 −25 ][ 14 −25 ]−[123 −615 ]+[ 70 07]
¿
[−724 −12
21 ] [ 12 15 ] [ 0 7 ]
−
3 −6 7 0
+
¿
[−312 −613 ]
Theorem
When f and g are polynomials over a field of scalars K and A is an n - square matrix over K then we
have
(i) ( f +g ) A=f ( A ) +g ( A)
(ii) fg ( A ) =f ( A) g( A)
(iii) ( kf ) A=kf ( A ) for k ∈ K
Note: Since f ( t ) g ( t )=g ( t ) f ( t ) for polynomials f (t)and g(t ), then f ( A ) g ( A ) =g ( A)f ( A).
This implies that for any two polynomials of matrix A they commute.
n n
Then by definition of f ( A)=a n A + ⋯ +a1 A+a 0 I and g( A)=bn A + ⋯ +b 1 A+ b0 I
n
Then ( f +g ) A=( an +bn ) A + ⋯ + ( a1+ b1 ) A + ( a 0 +b0 ) I
n n
So ( f +g ) A=a n A + bn A + ⋯ + a1 A +b1 A +a 0 I +b 0 I
¿ f ( A )+ g ( A)
Thus ( f +g ) A=f ( A ) +g ( A)
(ii) By definition
n+m
fg=C n+m t n +m + ⋯ + C1 t+C 0= ∑ C k t K
K=0
K
Where C K =a 0 b K + a1 bK −1+ ⋯ + aK b 0= ∑ ai bK −i
K=0
n+m
Hence fg ( A ) = ∑ C k A
K
K =0
( )(∑ )
n m
And f ( A ) g ( A ) = ∑ ai A i bj Aj
i=0 j=0
n m
¿ ∑ ∑ ai b j A i+ j
i=0 j=0
n +m
¿ ∑ C k A K =fg( A)
K=0
n n−1
Kf =K a n t + K an−1 t + ⋯ K a1 t+ K a0
n n−1
Where f ( t )=an t +a n−1 t + ⋯ + a1 t
n n−1
⟹ ( Kf ) A=K an A + K an−1 A + ⋯ K a1 A + K a 0 I
n n−1
¿ K (a¿¿ n A +a n−1 A + ⋯ a1 A+ a0 I )¿
¿ Kf ( A)
⇔ ( Kf ) A=Kf ( A )
LetT :V ⟶ V be a linear operator on a vector space V over a field of scalars K , a scalar λ ∈ K is called
an eigen value of T if there exists a nonzero vector V which is a member of a vector space V s.t
T ( v )=λv .
Note:
(i) Every vector that satisfies this relation is called an eigen vector of T belonging to eigen value λ .
(ii) Each vector Kv is an eigen vector s.t T ( Kv )=KT ( v )=K ( λv )=(Kv)
(iii) Terms like characteristic value/ proper value and characteristic vector/ proper vector are
synonymously used as eigen value and eigen vector respectively.
Example 1
We need the scalar t and a nonzero vector X = ( xy) s.t we have Ax=tx and since A=[ 13 24 ] we find
that: (13 24 )( xy)=t ( xy)
x +2 y=tx
3 x+ 2 y =ty
3 x+ ( 2−t ) y =0
For homogeneous equation to have a nonzero solution the determinant shoulb equal to zero (0).
|1−t3 2
2−t |
=0
( t+ 1 )( t−4 ) =0
So t=4 or t=−1
When t=4
( 1−4 ) x +2 y=0
−3 x+ ( 2−4 ) y=0
−3 x+ 2 y =0 ⋯ (1)
⟹ 3 x−2 y=0
x=2and y=3
X= ( xy)=(23)
The eigen vector V = ( xy )=(23) is the eigen value t=4
When t=−1
2 x+ 2 y =0
3 x+ 3 y=0
Thus v= (−11) or v=(−11 ) is a nonzero eigen vector belonging to the eigen value t=−1 and the other
eigen vector belonging to t=−1 is a multiple of v .
Let T :V → V be a linear operator on a vector space V with a finite dimension n and T can be
represented by a diagonal matrix
[ ]
K1 0 ⋯ 0
0 K2 ⋯ 0
⋯ ⋯ ⋯ ⋯
0 0 ⋯ Kn
T ( v 1 )=K 1 v 1
T ( v 2 )=K 2 v 2
⋯ ⋯⋯⋯
T ( v n )=K n v n
is such that the vectors v 1 , v 2 , ⋯ , v n are eigen vectors of the operator T belong to the eigen values
K 1 , K 2 , ⋯ , K n respectively.
Theorem
An n -square matrix A is similar to a diagonal matrix B iff A has n linearly independent eigen vectors in
this case the diagonal elements of B are the corresponding eigen values.
From the above theorem, if we let P be the matrix whose columns are the n independent eigen vectors
of A then B=P−1 AP
Example
Let A= (12 43).
(a) Find all eigenvalues of A and corresponding eigenvectors.
(b) Find an invertible matrix P such that P−1 AP is diagonal.
Solution
¿|t−1
−2
−4
t−3 |
¿ ( t−1 ) ( t−3 )−8
2
¿ t −4 t−5
¿(t−5)(t+1)
To obtain the eigenvectors belonging to the eigenvalue 5 we substitute t=5 in the characteristic
(−24 −4 x
2 y )( )
=0
4 x−4 y=0
−2 x+ 2 y =0
Or x− y =0
(−2
−2
−4 x
−4 y )( )
=0
−2 x−4 y=0
x +2 y=0
(b) Let P be the matrix whose columns are the above eigenvectors such that P= (11 −12 )
Then B=P−1 AP
( )(
1 2
¿
3
1
3 1 4 1 2
−1 2 3 1 −2 )( )
3 3
( )(
1 2
¿
3
1
3 5 −2
−1 5 1 )
3 3
¿ ( 50 −10 )
Bis a matrix representation of the operator A in the new basis.
−1
P AP is diagonal.
Question
[ ]
1 −3 3
Find all the eigenvalues and the basis of the following eigen space A= 3 −5 3
6 −6 4
[ ]
a11 a 12 ⋯ a1 n
a a 22 ⋯ a2 n
Where A= 21
⋯ ⋯ ⋯ ⋯
a n1 an 2 ⋯ ann
The matrix tI −A
Where I n is an n square identity matrix and t is a determinant called the Characteristic matrix of .
i.etI −A=¿
The determinant of the above ∆ A ( t )=det (t I n− A) or |tI − A| which is a polynomial in t is called a
Characteristic Polynomial of matrix A and we call ∆ A ( t )=|tI− A|=0 the characteristic equation of A .
Example
( )
1 3 0
Find the characteristic polynomial of A= −2 2 −1
4 0 −2
Solution
| |
t−1 −3 0
∆ t=tI − A= 2 t−2 1
−4 0 t+2
¿ ( t−1 ) ( t 2 −4 ) +6 t+12+12
3 2
¿ t −t −4 t +6 t +24
3 2
¿ t −t +2 t+ 24
Cayley-Hamiliton Theorem
Example
∆ t=|tI− A|
¿t (| 10 00)−(13 22)|
¿ |t−1
−3
−2
t−2 |
2
¿ t −3 t−4
But we are expected from Cayley-Hamiliton Theorem, A is a zero of its characteristic polynomial such
that ∆ t=t 2−3 t−4
( ) ( ) ( )
2
¿ 1 2 −3 1 2 −4 1 0
3 2 3 2 0 1
Note: There exists an intimate relationship between the characteristic polynomials and eigenvalues.
Theorem
Let A be an n square matrix over a field of scalars K . A scalar λ ∈ K is an eigenvalue of A if and only if
λ is a root of the characteristic polynomial ∆ (t)of A .
Corollary
Where a 1 , a2 , ⋯ , a n are distinct roots of ∆ (t), then A is similar to a diagonal matrix whose elements are
ai
Secondly: Let A be an n square matrix over the complex field C . Then A has at least one eigenvalue.
For example
( )
3 0 0
Let A= 0 2 −5 . We have its characteristic polynomial as ∆ (t) as
0 1 −2
| |
t−3 0 0
∆ t= 0 t−2 5
0 −1 t+2
¿ ( t−3 ) |t−2 5
−1 t+2|−0|
0 5
0 t+2|+ 0|
0
0
t−2
−1 |
¿ ( t−3 ) [ ( t −4 ) +5 ]=(t−3)(t +1)
2 2
3 2
¿ t −3 t +t−3
(i) A is a matrix over the real field; In this case A has only one eigenvalue 3. And since 3 has only
one independent eigenvector A is not diagonalizable.
(ii) A is a matrix over a complex field C then A has three distinct eigenvalues 3 , i and −i . Thus
there exists an invertible matrix P over a complex field C for which
( )
3 0 0
−1
P AP= 0 i 0
0 0 −i
Thus A is diagonalizable.
Question
Let A= (31 −1
1 )
and B=
1 −1
2 1 ( )
. Find all eigenvalues and corresponding eigenvectors of A and B
ANNIHILATORS
¿
When W is a subset of a vector space , a linear functional ∅ ∈V is called an Annihilator of W if
∅ ( w )=0 for every vector w ∈ W .
¿
i.e if ∅ ( w )={ 0 } a set of such matrix denoted by W 0 , the annihilator of W is a subspace/subset of V (a
dual space). This clearly shows that 0 ∈W 0 and that the subspace ∅ , δ ∈W 0 for every scalar a , b ∈ K
and every w ∈ W we then have:
( a ∅ +bδ ) W =a ∅ ( W )+ bδ(W )
¿ a .0+b .0
¿0
The concept of annihilator enables us to give another interpretation of a homogeneous system of linear
equations:
a 11 x 1 +a 12 x 2+ ⋯ +a 1n x n=0
a 21 x 1+ a22 x 2 + ⋯ + a2 n x n=0
a m 1 x 1+ am 2 x2 + ⋯ +a mn x n=0
Each row of coefficient matrix A=( aij ) is an element of K n and each solution of vector∅ =( x1 , x2 , ⋯ x n )
is viewed as an element of the dual space.
Example
Let W be the subspace of R4 , spanned by ( 1 , 2,−3 , 4 ) , ( 1 , 3 ,−2 , 6 )and ( 1 , 4 ,−1 ,8 ). Find the basis of
the annihilator W .
Solution
To find the basis, we shall have a set of linear functionals in the form
Where ∅ ( v 1 ) =0 , ∅ ( v 2 )=0 ∅ ( v3 ) =0
a+ 2b−2 c +4 d=0
b+ c+ 2d =0
2 b+2 c +4 d=0
∅ 1 ( x , y , , z , w )=5 x− y+ z
∅ 2 ( x , y , z , w ) =2 x + y
∅ 3 ( x , y , z , w )=2 y−w
Question
Given that W is a subspace of R3 spanned by (1 , 1, 0)and (0 , 1 ,1). Find the basis of the annihilator of
W.
Ans: ∅ ( x , y , z ) =x− y + z
Transposing a Linear mapping
Let T :V → U be an arbitrary mapping from a vector space V into a vector space U for any linear
¿
functional ∅ ∈U , the composition ∅ oT is a linear mapping from a vector space V into a field of scalars
K.
V U K
∅ oT
¿
⟹ ∅ oT ∈V corresponding to ∅ → ∅ oT which is a mapping T t →U ¿ → K ¿ and is defined by
t
T ( ∅ )= ∅ oT .
Note:
¿
For any scalars a , b ∈ K and any linear functionals∅ , δ ∈U
¿ a ( ∅ oT ) +b( δoT )
t t
¿ aT ( ∅ ) +b T ( δ )
t t t
Thus T ( a ∅ +bδ )=aT ( ∅ ) +b T (δ)
Hence T t is linear.
Example
Let ∅ be a linear functional on R2 defined by ∅ ( x , y )=x−2 y for each of the following linear operators
T on R2. Find [T ¿¿ t ( ∅ )](x , y )¿
(i) T ( x , y )=(x , 0)
(ii) T ( x , y )=(2 x−3 y , 5 x +2 y )
Solution
By definition: [T ¿¿ t ( ∅ )](x , y )= ∅ T (x , y )¿
¿ [x−(2)(0)]
¿x
Then[T ¿¿ t ( ∅ )]= ∅ T ( x , y )¿
¿ ∅ (2 x−3 y ,5 x +2 y)
¿ 2 x−3 y−2(5 x +2 y)
Activity
Solution
(i) T t ( ∅ )( x , y , z )= ∅ [ T ( x , y , z ) ] = ∅ [ x+ y , y + z ] =3 x+ 3 y −2 y−2 z =3 x + y −2 z
(ii) ∅ [ T ( x , y , z ) ] =∅ [ x + y + z ,2 x− y ]=3 x +3 y +3 z−4 x+2 y=−x +5 y +3 z
Note: We can emphasize that if T is a linear mapping from V into U then T t is a linear mapping from
¿ ¿
U into V i.e
U T V andV ¿ T t U ¿
Theorem
Let T :V → U be linear and let A be a matrix representation of A relative dual to the bases { v i } ∈ V and
{ ui } ∈ U .
Then the transpose matrix At is the matrix representation of T t :U ¿ → V ¿ relative dual to the bases{ ui }
and { v i }.
Practice exercise
LetT :V → U be linear and let T t :U ¿ → V ¿ be its transpose. Show that the kernel of T t is annihilator of
the image of T .
Solution
Supposing∅ ∈ker T t
¿ ( ∅ oT )( v )
¿ 0(v )
¿0
Secondly δ ∈ ( imT )0
i.eδ (imT )= { 0 } ∀ v ∈ V
⟹ [ T t ( δ ) ] ( v )=(δoT )v by definition
¿ δ (T (v ))
¿ 0(v )
[ T t ( δ ) ] ( v )=0
Hence T t ( δ )=0 ∴ δ ∈ ker T t
0 t
⟹ ( imT ) ⊂ ker T ⋯ ⋯ ⋯ ⋯ ⋯ ⋯ (2)
Let V be a vector space of definite and finite dimension of a field over K . A bilinear form on V is a
mapping f :V ×V → K and this satisfies
Note:
Example
The f is bilinear because ∅ and δ are each linear. Such bilinear form is called Tensor Product of ∅ and δ is
denoted by f = ∅ ⨂ δ
3. Let matrix A=( aij ) be an m ×n matrix over a field of scalars K , then A is seen as a bilinear
form on K n by defining
f ( x , y )=X t AY
( )( )
a 11 a12 ⋯ a 1n y1
¿( X 1 X 2 ⋯ X n ) a21 a22 ⋯ a 2n y2
⋯ ⋯ ⋯ ⋯ ⋮
a n 1 a n2 ⋯ ann y n
¿ a 11 X 1 y 1 +a 22 X 2 y 2+ ⋯ + ann X n y n
n
¿ ∑ aij X i y i
i , j=1
Examples
Solution
( )( )
3 −2 0 y 1
¿( x1 x 2 x 3 ) 5 7 −8 y 2
0 4 −1 y 3
2. Let A be an n × n matrix over a field of scalars K . show that f is a bilinear form on
n t
K :f ( X , Y )= X AY
Solution
n
Let any a , b ∈ K and X i Y i ∈ K
t
By definition f ( a X 1 +b X 2 , Y )=(a X 1+b X 2) AY
t t
¿(a X 1 +b X 2 ) AY
t t
¿ a X 1 AY + b X 2 AY ( By definition)
¿ af ( X 1 , Y ) +bf (X 2 ,Y )
Here f is linear in the first variable
t t t
Also f ( X , a Y 1+ b Y 2 )=X A ( a Y 1+ b Y 2 )=a X A Y 1 +b X A Y 2 (By definition)
¿ af ( X , Y 1 ) +bf (X ,Y 2)
f is linear in the second variable so f is in bilinear form on K n
v=b1 e 1+ b2 e2 + ⋯ +bn e n
¿ a 1 b1 ( e 1 ,e 1 ) +a 2 b 2 ( e 2 , e2 ) + ⋯ +an b n (e n , e n)
n
¿ ∑ a1 b j f (e i ,e j )
i , j=1
n
f ( u , v )= ∑ a1 b j f ( ei , e j )
i , j=1
()
b1
¿ ( a 1 a2 ⋯ an ) A b2
⋮
bn
t
¿ [u] e A v e ∀ u , v ∈V
Example
Solution
a 21=f ( u1 ,u 2 )=f [ ( 1 , 1 ) , ( 1 , 0 ) ] =2
a 11=f ( u2 ,u2 ) =f [ ( 1 ,1 ) , ( 1 ,1 ) ] =0
(c) Write v 1 and v 2 in terms of ui in order to get the transition matrix P from one basis to another.
For instance v 1=( 2 ,1 ) =( 1, 0 )+ (1 , 1 )=u1 +u2
v 2=( 1 ,−1 )=2 ( 1 , 0 )−( 1 , 1 )=2 u1−u2
From above
u1 +u2
2 u1−u2
=
}[
1 1
2 −1
=P ]
P=
t
[ 11 −12 ]
SYMETRIC BILINEAR FORMS
Note:
t t t
X AY and therefore equals to its transpose if f is symmetric then Y A X=f ( X ,Y )=f ( Y , X ) =Y AX
t
Theorem
Let f be the symmetric bilinear form of vector space V over a field of scalars K and where 1+1 ≠0 .
Then V has a basis { v 1 , v2 , ⋯ , v n } in which f is represented by a diagonal matrix
i.e f ( v i , v j ) =0 for i≠ j
In other words let A be a symmetric matrix over K (Where 1+1 ≠0 ) then there exists nonsingular
Note: One way of obtaining the diagonal form of Pt AP is by a sequence of elementary row operations
and the same sequence of the elementary column operations. These operations on I , an identity matrix
will yield Pt .
( )
1 2 −3
For instance: Let M = 2 5 −4 , a symmetric matrix forming a block matrix (M , I ) gives
−3 −4 8
( | )
1 2 −3 1 0 0
( M , I )= 2 5 −4 0 1 0
−3 −4 8 0 0 1
( | )
1 2 −3 1 0 0
Applying R2 →2 R1 + R2∧R 3 → 3 R 1+ R 3 we get 0 1 2 −2 1 0
0 2 −1 3 0 1
( | )
1 0 0 1 0 0
0 1 2 −2 1 0
0 2 −1 3 0 1
( | )
1 0 0 1 0 0
0 1 2 −2 1 0
0 0 −5 7 −2 1
( | )
1 0 0 1 0 0
0 1 0 −2 1 0
0 0 −5 7 −2 0
[ ]
1 0 0
The matrix c has been diagonalizedsosetting P= −2 1 0
7 −2 1
[ ]
1 −2 7
t
P = 0 1 −2
0 0 1
[ ]
1 0 0
t
P AP= 0 1 0
0 0 −5
QUADRATIC FORM
Definition: A mapping q :V → K is a quadratic form if q ( v )=f ( v , v) for some symmetric bilinear form
on V . q is called quadratic form associated with symmetric bilinear form f when 1+1 ≠0 in K then f
1
can be obtained from q in accordance to the identity f ( u , v )= q ( u+ v )−q (u )−q (v ).
2
For instance: let the mapping f be represented by a symmetric matrix A=(aij ). Then the mapping q can
be represented by q ( x )=f ( X , X )= X t AX
( )( )
a11 a12 ⋯ a1 n X 1
¿ ( x1 x2 ⋯ xn ) a 21 a22 ⋯ a2 n X 2
⋯ ⋯ ⋯ ⋯ ⋮
an 1 an 2 ⋯ a nn X n
n
¿ ∑ aij X i X j
i , j=1
Example
Find the symmetric matrix corresponding to each of the following quadratic polynomials
1. q ( x , y )=4 x 2−6 xy +7 y 2
2. q ( x , y )=xy + y 2
3. q ( x , y , z )=3 x 2 +4 xy − y 2+ 8 xz−6 yz + z 2
Solution
Note: The symmetric matrix A=( aij ) which represents q (x 1 , x 2 , ⋯ , x n ) has a diagonal entry a ii equal to
2
the coefficient X 1 has the entries a ij and a ji each equal to half the coefficient of X i X j.
1 1
Other entries are and
2 2
( )
1
0
2
⟹ The required matrix is A=
1
1
2
3. q ( x , y , z )=3 x 2 +4 xy − y 2+ 8 xz−6 yz + z 2
⟹ The diagonal elements are 3 ,−1 and 1
The entries for a 12 and a 21=¿ half the coefficient of 4 xy ; 2 and 2
For a 31 and a 13=¿ half the coefficient of 8 xz ; 4∧4
For a 23 and a 32=¿ half the coefficient of −6 yz ;−3∧−3
[ ]
3 2 4
Therefore the required matrix A= 2 −1 −3
4 −3 1
4. Find the required matrix A , given that q ( x , y , z )=x 2−2 yz + xz
⟹ The diagonal entries are 1 , 0∧0
The entries for a 12 and a 21 are the half coefficients of 0
1
a 31anda 13 are the half coefficients of xz=
2
a 32anda 23 are the coefficients of yz=−1
[ ]
1
1 0
2
⟹ The required matrix A= 0 0 −1
1
−1 0
2
5. Find a non singular matrix P such that Pt AP is diagonal for each of the following real
symmetric matrices A and also find its signature.
[ ] [ ]
1 −3 2 0 1 1
A= −3 7 −5 and A= 1 −2 2
2 −5 8 1 2 −1
HINT: Signature=No of positive entries−No of negative entries for a diagonal ¿
Answer: Signatureis 1
HERMITIAN FORMS
By letting f :V ×V → C s.t
(ii) f ( u , v )=f (u , v )
(iii) f ( u ,a v 1+ b v 2 ) =f (a v 1 +b v 2 , u)
¿ af ( v 1 , u ) + bf (v 2 , u)
¿ a f ( v 1 ,u ) +b f (v 2 , u)
¿ a f ( u , v 1 ) +b f (u , v 2)
Thus f ( u ,a v 1+ b v 2 ) =a f ( u , v 1 ) + b f (u , v 2)
Note
In condition (i) f is linear in the first variable and in condition (ii) f is conjugate linear in the second
variable.
By condition (ii) f ( v , v )=f ( v , v ) so that f (v , v ) is real for each and every vector v ∈ V
For instance Let A=(a¿¿ ij)¿ be an n × n matrix over C we can write A for the matrix obtained by
taking a complex conjugate of every entry of A i.e A=( a¿¿ ij)¿
¿
Also we can write A for A−t= A t
Solution
∀ a , b ∈C and ∀ X 1 , X 2 ,Y ∈C n
We define
t
f ( a X 1 +b X 2 , Y )=(a X 1+b X 2) A Y
t t
¿(a X 1 +b X 2 ) A Y
¿ af ( X 1 , Y ) +bf (X 2 ,Y ) By definition
Hence f ( a X 1 +b X 2 , Y )=af ( X 1 ,Y ) + bf (X 2 , Y )
Also f ( X ,Y ) =X t A Y
t t
¿( X A Y )
t t
¿Y A X
t ¿
¿Y A X
Hence f ( X ,Y ) =f (Y , X )
Note: A real matrix is Hermitian if and only if it is symmetric (i.e the symmetric matrices A=A t )
Example
( )
2 2+3 i 4−5 i
1. Determine whether A= 2−3 i 5 6+2 i is Hermitian?
4+5 i 6−2i −7
Solution
¿
The condition matrix A=( aij ) is Hermitian if and only if A=A i.ea ij=a ji
( )
2 2+3 i 4−5 i
Since A= 2−3 i 5 6+2 i
4+5 i 6−2i −7
( )
2 2−3 i 4+5 i
Conjugate of A= 2+3 i 5 6+2 i
4−5i 6−2i −7
( )
2 2+3 i 4−5i
Transpose of conjugate 2−3i 5 6+2 i = A
4 +5 i 6−2i −7
¿
Since A = A . Then A is Hermitian (Since it is equal to its conjugate’s transpose)
( )
1
1+i 2i
2. Let H= 1−i 4 2−3i be a Hermitian matrix. Find a non singular such that Pt H P.
−2 i 2+3 i 7
Find its signature.
Solution
( | )
1 1+i 2i 1 0 0
Block matrix(HI)¿ 1−i 4 2−3 i 0 1 0
−2i 2+ 3i 7 0 0 1
Apply row operations R2 → R2 +(−1+i) R1
R3 → R 2+2 i R 1
( | )
1 1+i 2i 1 0 0
¿ 0 2 −5i −i+1 1 0
0 5i 3 2i 0 1
Now applying corresponding Hermitian column operations as
C 2 → (−1−i ) C 1 +C 2
C 3 →−2i C1 +C 3
( | )
1 0 0 1 0 0
Gives 0 2 −5 i −1+i 1 0
0 5i 3 2i 0 1
Applying R3 →−5 i R2 +2 R3
( | )
1 0 0 1 0 0
0 2 −5 i −1+i 1 0
0 0 19 5+ 9 i −5 i 2
( | )
1 0 0 1 0 0
0 2 0 −1+i 1 0
0 0 −38 5+9 i −5 i 2
( )
1 0 0
P= −1+i 1 0
5+9 i −5 i 2
( )
1 −1+i 5+ 9 i
t
⟹ H has been diagonalised so setting P = 0 1 −5 i
0 0 2
( )( )( )
1 −1+ i 5+9 i 1 1+i 2i 1 0 0
t
Then P H P= 0 1 −5i 1−i 4 2−3 i −1−i 1 0
0 0 2 −2i 2+ 3i 7 5−9 i 5 i 2
PRACTICE QUESTIONS
For each of the following Hermitian matrices find a non singular matrix P such that Pt H P is diagonal.
(a) H=(−i1 2i )
(b) H=(
2−3i −1 )
1 2+ 3i
[ ]
1i 2+ i
(c) H= −i 2 1−i
2−i 1+i 2